Pelecehan Seksual Pada Anak - Fitriana Maghdalena; Zulkipli Lessy (Lembaga Pengembangan Kinerja Dosen, 2024)
This study discusses Sexual Abuse in Children. This research is a qualitative research with a literature review approach. In this study, research data were obtained from one source, namely secondary data in the form of journal articles, books, conference papers, theses, and other sources, authors can produce a scientific work that has several main points from the title above. Some of these points are understanding the concept of reducing sexual activity in children and efforts to prevent sexual deception in children.